Fontes alternativas de potássio para soqueira da cana-de-açúcar - Marques, Eduardo Parra (2021)
Being in a prominent position as the source of renewable energy in Brazil and in the world, sugar cane producers are looking for growing productivity that increasingly demand from plants that tend to deplete nutrients from the soil. Potassium being (K), the most required and important nutrient in this cultivation. Concentrated and repeated fertilisers, provide serious problems to the soil, so that the verticalization of the production occurs it is necessary to find new methodologies and technologies. Therefore, the objective of this study was to evaluate the effect of potassium sources and their impacts on soil fertility, productivity, physiological, technological and nutrional parameters of sugar cane, first sprout, in Cerrado edaphoclimatic conditions. Two experiments were carried out at Goiasa factory, in Goiatuba, GO, during the harvest 2019/20, being in a PLINTOSOLO HÁPLICO and the other in a LATOSSOLO VERMELHO, using the sugar cane variety SP83-2847. The treatments consisted of four sources of potassium (KCl, vinasse, rock powder and polysulfate), and a control that did not receive application of the nutrient, arranged in randomized blocks with five repetitions. The treatments were applied at the dose of 120 kg of K2O per ha, superficially, over the cane line, at 30 days after sprouting (DAS). It was evaluated: K content in the soil (up to 0.8 m) and in the plant (leaf and stalk); biometric variables (plant height, stalk diameter and number of tillers), stalk production and technological quality of stalks. In PLINTOSSOLO HÁPLICO KCl increased potassium levels to 180 DAS in the 0-0.2 m depth layer significantly. However, in the 0.2-0.4 and 0.4-0.6 m layers, at 180 DAS, the vinasse that had a significant effect. At 295 DAS the KCl in the 0.2-0.4 layer m of depth, provided an increase in the potassium content in the soil. Already in LATOSSOLO VERMELHO, at 180 DAS, were elevated in the 0-0.2 m layer by KCl and 0.2-0.4 m through vinasse. After 295 days, KCl still had an effect on layer 0-0.2m, but in the 0.2-0.4 m layer the polysulfate that started to present the best result for soil K content. The saturation of CEC by potassium, increased in all treatments in PLINTICO soil and decrease in LATOSSOLO, the same effect it happened with potassium levels in the soil at all depths. At the PLINTOSSOLO HÁPLICO occurred the biggest accumulations of potassium in the stalk for all potassium applications. And the largest exports of the nutrient were from sources polysulfate, KCl and rock powder. The use of rock powder also provided gains in the technological quality of sugarcane in first cut located in LATOSSOLO VERMELHO. The stalk production was influenced by KCl and polysulfate, in both soils, providing the highest yields.